PreEve - Preschool event mobile application / Nor Afiifah Zainudin - Zainudin, Nor Afiifah (2021)
Over the last years, event management has become a flourishing sector of the education industry and a natural feature of the leisure programs of schools, colleges, and universities. Consequently, most event preparation classes are lecture-based courses with class activity preparation for fictional activities. Therefore, to manage the preschool event which the teachers need to plan and execute a “real” event is a more meaningful and productive way to learn how to make a successful event. But, there is a certain educational organization use manual invitation which is hand-by-hand such as flyers, cards, and posters to promote their school's activities. There are several issues for this project is the teacher have no defined platform to send notification about the events that’s make some of the parents does not notice or know and/or overlooked the event that has been announced by the teacher, some of the parents sometimes tend to forget the date, time and/or venue of the event and ensuring that interaction or communication between the teachers and the parent is open and available. Therefore, this project aims to develop a mobile application with a push notification service to notify and assist the parent to get alert with any events from the teacher. The push notification used in this application is via Firebase Cloud Messaging (FCM). By using this application, a parent can get notifications about the events and track activity held by the preschool. Mobile Application Development Life Cycle (MADLC) Model is the method used for this project. However, this project will be developing up until the testing phase only. The outcome is reached based on the outcomes, which means that the parent is more notified and can be more aware to prepare for the upcoming event.